Promoter DNA hypermethylation – Implications for Alzheimer's disease. (15th October 2019) - Liu, Yiyuan; Wang, Minghui; Marcora, Edoardo M.; Zhang, Bin; Goate, Alison M.
Highlights: Hypermethylation dominates promoter DNA alterations in AD (94 of 118 genes). Promoter hypermethylated genes are enriched for transcription factor targets and regulators of proliferation, signaling and stress response. Cell type-specific expression was considered to prioritize genes with AD functional relevance in microglia, astrocytes and neurons. Abstract: Recent methylome-wide association studies (MWAS) in humans have solidified the concept that aberrant DNA methylation is associated with Alzheimer's disease (AD). We summarize these findings to improve the understanding of mechanisms governing DNA methylation pertinent to transcriptional regulation, with an emphasis of AD-associated promoter DNA hypermethylation, which establishes an epigenetic barrier for transcriptional activation. By considering brain cell type specific expression profiles that have been published only for non-demented individuals, we detail functional activities of selected neuron, microglia, and astrocyte-enriched genes ( AGAP2, DUSP6 and GPR37L1, respectively), which are DNA hypermethylated at promoters in AD. We highlight future directions in MWAS including experimental confirmation, functional relevance to AD, cell type-specific temporal characterization, and mechanism investigation.